Counting the costs of cancer care: breast, cervical and lung cancer in Trent - Wolstenholme, Jane (2001)
The purpose of this thesis is to explore the theory, practice and application of costing with specific reference to cancer. In part it reviews the theory and guidelines related to costing methods including the recent focus on the analytical techniques used with cost data. In addition it examines how these theories and guidelines are applied in practice, by reviewing the literature on costs and cancer. The empirical research in this thesis applies costing methods to three specific cancer sites; breast, cervix and lung. This analysis provides information on the total burden of these specified cancers in terms of cost to a typical health authority (Trent). It also explores the hypothesis highlighted in previous studies that the cost of cancer increases with the stage of the disease. The final area of contribution for the thesis is in the application of recently suggested analytical techniques for cost data to the breast, cervical and lung cancer data sets; it investigates a number of proposed techniques for the analysis of skewed cost data and methods for data with incomplete patient follow up.